Design, synthesis and validation of anti-microbial coumarin derivatives: An efficient green approach. Issue 10 (October 2019) - Khan, Mohd. Shahnawaz; Agrawal, Ranu; Ubaidullah, Mohd; Hassan, Md. Imtaiyaz; Tarannum, Nazia
Abstract: An ecofriendly itinerary for the synthesis of newly substituted chromene-3-carboxamide derivatives was undertaken to avoid impurities, usage of toxic solvents, toxic catalyst, and having improved quantitative yields. The green synthesis involves the condensation of substituted salicylaldehyde with N-(substituted)phenyl malonic acid in the presence of a base catalyst, piperidine. All reported compounds were assessed for their antimicrobial activities which clearly suggested their therapeutic implications to address antimicrobial pathogenesis. The synthesized coumarin compounds were examined for their antimicrobial activity against 7 fungal strains and 2 bacterial strains at concentration 125–1000 μg/mL. In particular, the compounds 4 and 5 showed lower minimum inhibitory concentration value (125 μg/mL) against maximum microbial strains. Further, docking of all the synthesized compounds was performed with the enzymes lanosterol 14α-demethylase and glucosamine-6-phosphate synthase and a significant binding affinity was observed which supports in vivo antimicrobial study. In addition, the thermal analysis revealed good thermal stability of compounds up to 250 °C. The compounds showed abroad absorption spectrum between 280-550 nm establishing them to be good UV absorbers. Abstract : Organic chemistry; Pharmaceutical chemistry; Green synthesis; Substituted coumarin derivatives; Molecular docking; Antimicrobial activity; Drug design and discovery; Minimum inhibitory concentration.